SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PEGAWAI TERBAIK PADA BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KOTA PARIAMAN MENGGUNAKAN METODE SIMPLE ADDITVE WEIGHTING - man, ar (STKIP PGRI Sumatera Barat, 2020)
Badan The Pariaman City Regional Disaster Management Agency (BPBD) is a government agency in the city of Pariaman, consisting of employees and honorary. So that employee performance can be better every year, holding the best employee selection. Problems that occur in the process of selecting the best employees so far are, data processing is still manual so it takes a long time, giving value to employees is still in the form of paper files so prone to data loss, limited employee assessment criteria in BPBD Kota Pariaman. In research the research method uses the SDLC approach and system design aids using UML. Based on permaslah above, researchers provide a solution by designing a decision support system for selecting the best employees using the SAW method. The result with the best employee selection SPK system in Pariaman BPBD can also minimize the risk of losing employee data, making the best employee selection evaluation criteria in accordance with criteria set by the custodian, besides that with this SPK the selection of the best employees is more effectivefs